Community Empowerment Strategies through the Role of Female Preachers in KOAS Communities in the Air Joman District - Eriza Ricki Rahmayani Lubis; Salamuddin Salamuddin (UNIVERSITAS PAKUAN, 2023)
KOAS (Community of Akhwat Sholihah) is a Taklim assembly that functions as a community founded to nurture and propagate Islamic teachings. This empowerment initiative aims to not only develop the economic potential of the community but also enhance dignity, boost self-confidence, preserve local cultural values, and promote a return to divine values based on Islamic principles, referred to as divine values. The research conducted is descriptive in nature and employs qualitative techniques, utilizing data sources from interviews, photographs, and observations. The research findings are closely tied to the community empowerment strategy implemented by KOAS. This strategy involves providing intensive coaching within the community, cultivating a belief within the community that Islam offers solutions for life, and delivering sermons within the community.